Morphometric and histological characteristics of the stomach and reproductive organs in Japanese quail - Dramou Foromo; Ezeldien Sahar; Ziad Ahmad Alabdallah; S.B. Seleznev (Caspian Journal of Environmental Sciences)
Knowledge of the anatomical features of the digestive and reproductive systems in Japanese quails makes it possible to purposefully influence their growth and development, using breeding and selection in the right direction to preserve the health of animal and increase its productivity. Japanese quail at certain stages of postembryonic ontogenesis—neonatal (daily), juvenile (30 days), puberty (60 days), and morpho-functional maturity (90 and 240 days) were used in this study. A morphometric assessment of the stomach, ovary, and testes of Japanese quails and the development of its linear index were analysed based on the obtained data. Also, a histological study at different ages was conducted. The materials included the glandular and muscular sections of the stomach, ovaries, and testes obtained from clinically healthy Japanese quails. The material was taken in the middle of a certain stage of postembryonic ontogenesis and consisted of 10 specimens for each age group. The dissected organs of Japanese quails was weighed on an electronic balance to determine the absolute weight in grams. Next, the relative weight of the organ was calculated. Additionally, venire calipers were used to measure the studied organs length and width. In addition to studying the histological structure of the stomach, ovary, and testes. The Japanese quail's stomach was characterized by an age-related staging of formation, with the glandular part growing most intensively until 30 days and the muscular part forming only at 90 days. In the case of histological study, in the glandular stomach, the submucosal layer occupied an average of 63.03% of the total surface area on the 90th day, while the muscle layer increased by 6.32%, equivalent to an increase of 1.98 times. As for the muscular stomach. The rate of development of the inner layer of the muscular stomach varied from day 1 to day 720, increasing its surface area by 10.01 ± 0. A direct correlation between avian reproductive health, ovarian and testicular mass was recorded. Quail mature sexually between four and five weeks of age. At around 6 weeks of age, females begun to lay. In the time between 60 and 150 days of age, the ovary developed most rapidly.